Women, sport, and society in modern China : holding up more than half the sky - Dong, Jinxia, 1962- (Sport in the global society., 2003)
Drawing on Chinese sources hitherto unavailable in the West, official documents and interviews with top athletes, the author explores the rise of Chinese super sportswomen.